Electrocoagulation for Cattle Slaughterhouse Wastewater Management: A Review of Technologies and Treatment Parameters - Sugiharta, Iip; Kiswandono, Agung Abadi; Pandiangan, Kamisah Delilawati; Simanjuntak, Wasinton (Indonesian Journal of Chemistry, 2025)
The management of slaughterhouse wastewater presents significant environmental challenges due to its high organic load, fat, oil, and persistent pollutants. Electrocoagulation (EC) is an effective treatment method that utilizes electric currents to generate in situ coagulants for pollutant removal. This review examines key operational parameters of EC, including current density, pH, electrode type, and contact time, while comparing its performance with electro-oxidation (EO) and coagulation-flocculation (CF). The findings indicate that EC effectively reduces Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and turbidity with relatively low operational costs. Integrating EC with CF and EO improves treatment efficiency by addressing complex wastewater characteristics. Optimization of parameters, energy consumption reduction, and electrode durability enhancements are recommended for improving EC performance. Bibliometric analysis using VOSviewer highlights the increasing research focus on energy efficiency, electrode materials, and process optimization. A graphical abstract is provided to illustrate EC’s role in wastewater treatment, highlighting its effectiveness, optimization strategies, and integration potential. Future research should focus on scaling up industrial applications and integrating predictive models to enhance efficiency and sustainability in slaughterhouse wastewater management.